Pengetahuan Pemanfaatan Media Sosial Sebagai Media Pembelajaran Siswa - Siswi Sekolah Islam Imam Syafi'i - Rengga Herdiansyah; Cholis Hanifurohman; Debby Rahadian Baskhara (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The use of social media has become important in the daily lives of modern society, including students at the Imam Syafi'i Islamic School. This reflects major changes in the world of education, where information and communications technology, especially social media, is playing an important role in the way we learn and interact with each other. Educators consider community service programs to be very important in facing this digital era. As an educational institution, the Imam Syafi'i Islamic School has a big role in shaping the character and knowledge of its students. The success of the learning process in this school really depends on the ability of educators to keep up with technological advances, especially the use of social media. Preliminary analysis shows that Imam Syafi'i Islamic School students widely use social media, but further research is needed to incorporate it into the learning process further. Attention to the use of social media in education has increased in recent years. It is very important for educators at the Imam Syafi'i Islamic School to understand how to utilize social media in the learning process because research shows that it can increase student engagement, motivate them to learn, and enable them to work together. With this service to society, the main thing we want to help is how we can inform the students of Imam Syafi'i Islamic School about how to use social media as an effective learning tool and how best to use social media morally and productively. The main aim of this community service project is to increase the understanding of Imam Syafi'i Islamic School students about social media as an effective learning tool. The project also aims to provide guidance to educators on how best to incorporate social media into their daily activities. The output to be achieved in this community service is a national journal and online media.